2011
DOI: 10.1111/j.1540-4560.2011.01726.x
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Identity Threat: The Role of Cultural Identifications in Moderating Closure Responses to Foreign Cultural Inflow

Abstract: Political theorists of globalization have argued that foreign inflows to a society can give rise to collective‐identity closure—social movements aiming to narrow the in‐group, and exclude minorities. In this research we investigate whether exposure to the mixing of a foreign culture with one's heritage culture can evoke need for closure, a motive that engenders ethnocentric social judgments. On the basis of a proposed identity threat mechanism, we tested the hypothesis that exposure to situations mixing foreig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 43 publications
1
60
0
2
Order By: Relevance
“…Tadmor, Hong, Chao, Wiruchnipawan, and Wang (2012) investigated the impact of exposure to multiculturalism on prejudice, through reduced levels of NFC. Although previous research has suggested that subtle exposure to culture mixing may increase individuals' levels of NFC (Morris, Mok, & Mor, 2011), Tadmor and colleagues argued that when immersed in an unfamiliar multicultural environment, reliance on automatic processes and schemas formed by socialization within one's own familiar culture becomes insufficient. Further, as multicultural experiences accumulate, so does the new information that is distinct, inconsistent, or even contradictory to internalized schemas of the relevant culture.…”
Section: Reduction Of Nfc and Prejudice Through Multicultural Experiementioning
confidence: 98%
“…Tadmor, Hong, Chao, Wiruchnipawan, and Wang (2012) investigated the impact of exposure to multiculturalism on prejudice, through reduced levels of NFC. Although previous research has suggested that subtle exposure to culture mixing may increase individuals' levels of NFC (Morris, Mok, & Mor, 2011), Tadmor and colleagues argued that when immersed in an unfamiliar multicultural environment, reliance on automatic processes and schemas formed by socialization within one's own familiar culture becomes insufficient. Further, as multicultural experiences accumulate, so does the new information that is distinct, inconsistent, or even contradictory to internalized schemas of the relevant culture.…”
Section: Reduction Of Nfc and Prejudice Through Multicultural Experiementioning
confidence: 98%
“…Being closely identified with one's own social group and its culture makes categorization a natural process when the impression of one's own culture is juxtaposed against the impression of a foreign one. Moreover, it is unlikely for individuals to react defensively and impulsively against a transaction between two social groups if they are not personally attached to and invested in one of the social groups and its culture—especially if they are not an integral part of the transaction and will not be economically affected by it (Morris, Mok, & Mor, 2011).…”
Section: Conditions That Heighten the Perceived Threats To Cultural Imentioning
confidence: 99%
“…It reflects the narrowing of the cultural mind, with an ethnocentric, essentialized approach to guarding one's cultural status, adhering to behavioral ideals of local culture, and resisting multicultural environments and intercultural exchanges. These individuals may not react negatively to stimuli from a single foreign culture stimuli, but rather to mixing their own culture's iconic image with that of another culture (Morris, Mok, & Mor, 2011;Torelli et al, 2011). They are anxious about losing their culture's borders and unwilling to leave their comfort zone to embrace novelty.…”
Section: Ethnic Protectionmentioning
confidence: 99%